2022
DOI: 10.1155/2022/6118660
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Propolis Extract (Caffeic Acid Phenethyl Ester) Addition on the Candida albicans Adhesion and Surface Properties of Autopolymerized Acrylic Resin

Abstract: Background. Denture stomatitis has been linked to the adhesion and proliferation of Candida albicans (C. albicans) on denture bases, which is a common and recurrent problem in denture wearers. The current study aimed to evaluate the effect of incorporating caffeic acid phenethyl ester (CAPE) into autopolymerized polymethyl methacrylate (PMMA) acrylic resin on C. albicans adhesion, surface roughness, and hardness as well as the correlation between tested properties. Methods. Autopolymerized acrylic resin discs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…Reducing the number of molecular chains per cross-sectional area unit and reducing the number of connections reduces the surface roughness [24,25] . However, unlike the results of the present study, the results of a study by Al-Khalifa et al (2022) revealed an increase in surface roughness due to the addition of 2.5% of propolis extract (CAPE) in auto-polymerized acrylic resin [26] . The reason for this difference can be related to the type of substance under investigation and the type of extract in this study.…”
Section: Effect Of Disinfection On Surface Roughness Of Polycarbonatecontrasting
confidence: 99%
See 1 more Smart Citation
“…Reducing the number of molecular chains per cross-sectional area unit and reducing the number of connections reduces the surface roughness [24,25] . However, unlike the results of the present study, the results of a study by Al-Khalifa et al (2022) revealed an increase in surface roughness due to the addition of 2.5% of propolis extract (CAPE) in auto-polymerized acrylic resin [26] . The reason for this difference can be related to the type of substance under investigation and the type of extract in this study.…”
Section: Effect Of Disinfection On Surface Roughness Of Polycarbonatecontrasting
confidence: 99%
“…However, chlorhexidine solution reduces the micro-hardness of root dentin [30] . The study by Al-Khalifa et al (2022) also showed a reduction in the hardness of acrylic resin with the addition of propolis extract (CAPE) [26] . Hardness is defined as a material's resistance to wear opposing tooth structures.…”
Section: Effect Of Disinfection On Hardness Of Polycarbonatementioning
confidence: 97%
“…Also, the powerful antimicrobial properties of EGCG against E. faecalis and S. mutans as well as its suppressive effects on their virulence genes have been verified by multiple studies [63]. [64]. Propolis in the form of ethanol extract (EEPs) is an herboriginated nontoxic product that is usually used as a dietary supplement and antibacterial agent [65].…”
Section: Herbal and Natural Materials In Oral Biofilm Treatmentsmentioning
confidence: 97%
“…A previous CAPE study demonstrated effective antifungal action against C. albicans . Biofilm formation and hyphal growth of C. albicans are inhibited by it as well [ 64 ]. Propolis in the form of ethanol extract (EEPs) is an herb-originated nontoxic product that is usually used as a dietary supplement and antibacterial agent [ 65 ].…”
Section: Herbal and Natural Materials In Oral Biofilm Treatmentsmentioning
confidence: 99%
“…Surface properties are considered the most important factor in C. albicans adhesion and colonization, along with other factors such as poor oral hygiene and ill-fitting dentures ( 2 ). It was reported that DS occurrence rate is about 30%–75% of denture wearers and high recurrence rate even with antifungal treatment ( 3 ). This situation increased as the surface properties change (increasing Ra and contact angle and decreasing hardness) where rougher surfaces act as a nest and become an adequate environment for microbial adhesion and colonization ( 2 ).…”
Section: Introductionmentioning
confidence: 99%